Effect of pegylated interferon-α2b add-on therapy on renal function in chronic hepatitis B patients: A real-world experience - Peng, Mei-Juan; Guo, Xiao-Qing; Zhang, Wei-Lu; Chen, Jing; Kang, Wen; Yang, Xiao-Fei; Guo, Ying; Zhang, Ye (Frontiers in Microbiology, 2022)
Background and aim Controversy remains as to pegylated interferon-α (PEG-IFNα) antiviral therapy to renal function in chronic hepatitis B (CHB) patients. The aim of this study was to evaluate the influence of PEG-IFNα2b (Y shape, 40 kD) add-on treatment for renal function in CHB patients who received entecavir therapy. Methods This was a retrospective observational study to investigate factors related to renal function in 114 CHB patients who received PEG-IFNα2b add-on therapy to entecavir for 48 weeks. Changes of blood urea nitrogen (BUN), serum creatinine (sCr), and estimated glomerular filtration rate (eGFR), which was calculated with both Chronic Kidney Disease Epidemiology Collaboration and Modification of Diet in Renal Disease (MDRD) formulas, were analyzed by one-way analysis of variance. A linear mixed effects model for repeated measures was used to assess the correlation between baseline information and eGFR changes at 24 and 48 weeks of therapy. The model considered the baseline age, gender, body weight, viral load, hepatitis B surface antigen, BUN, sCr, and treatment strategy as fixed effects and incorporated random effects for individual subjects. Results BUN and sCr was decreased, while eGFR was increased at 12 weeks of therapy. Only eGFR maintained at 24 and 48 weeks of therapy. Patients with female gender, age ≥ 40 years, and baseline HBsAg level < 250 IU/mL showed significant improvement of renal function with PEG-IFNα2b add-on therapy. The linear mixed effects model revealed that female gender, baseline sCr, and PEG-IFNα2b add-on were significant positive predictors for eGFR elevation at 24 and 48 weeks of therapy. Conclusion In real-world experience, PEG-IFNα2b add-on therapy might be associated with increased eGFR in CHB patients.